Online Social Media Applications for Constructivism and Observational Learning - Mbati, Lydia (International Review of Research in Open and Distributed Learning, 2013)
Web 2.0 technologies have a range of possibilities for fostering constructivist learning and observational learning. This is due to the available applications which allow for synchronous and asynchronous interaction and the sharing of knowledge between users. Web 2.0 tools include online social media applications which have potential pedagogical benefits. Despite these potential benefits, there is inadequate utilization of online social media applications in learning management systems for pedagogical purposes. Reasons cited for the limited uptake of online social media applications in learning management systems include the lack of consideration regarding the pedagogical benefits of these applications (Christie & Garrote-Jurado, 2009, pp. 273-279). There is limited information regarding experiences of the use of online social media that foster constructivist and observational learning. Using a qualitative meta-ethnographic approach, this article explores the experiences of students and instructors regarding online social media applications for constructivism and observational learning. Constructivist criteria (Baviskar, Hartle, & Whitney, 2009, pp. 543-544) and observational learning, based on Bandura’s (2001, pp. 265-299) social cognitive theory, formed the theoretical grounding for this research. The findings suggest that discussion forums are ideal for the stimulation of constructivism and observational learning in online learning programmes.